2020
DOI: 10.1186/s13020-020-00393-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-COVID-19 drug screening: Frontier concepts and core technologies

Abstract: The outbreak of COVID-19 has recently evolved into a global pandemic. Up to July 2020, almost every country has confirmed COVID-19 cases reported worldwide. Many leading experts have predicted that the epidemic will persist for relatively a long period of time. Thus far, there have been no remedies proven effective against the disease. As the nation where COVID-19 broke out first, China has adopted a combination of traditional Chinese medicine and western medicine to fight against the disease, and has achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This brings uncertainty in the drug market, and with COVID-19, many products became high-priced. During the time of COVID-19, all the big pharmaceutical companies, whether Indian or locally owned, were challenged by the export restrictions imposed by India and many other supplying countries [14]. This led to shortage of drugs and other health commodities in the Rwandan market.…”
Section: Challengesmentioning
confidence: 99%
“…This brings uncertainty in the drug market, and with COVID-19, many products became high-priced. During the time of COVID-19, all the big pharmaceutical companies, whether Indian or locally owned, were challenged by the export restrictions imposed by India and many other supplying countries [14]. This led to shortage of drugs and other health commodities in the Rwandan market.…”
Section: Challengesmentioning
confidence: 99%
“…The global SARS-CoV-2 pandemic has resulted in widespread activities seeking to identify new anti-viral drugs that might be used to treat COVID-19 patients [ 1 5 ]. Remdesivir has emerged as a lead candidate with clear anti-viral activity in vitro [ 6 ] and non-human primates [ 7 ], with results in human trials suggesting benefit, although mortality remained high [ 8 , 9 ].…”
Section: Main Textmentioning
confidence: 99%
“…Recently, Battagello et al, (2020) compiled information on the importance of cell stress signals throughout the SARS-CoV-2 illness; penetration and replication in cells, and suggested that the presence of clinical manifestations in individual patients was due to the infection's transcendent injury and attack on cells (Chen et al, 2020b). Increased mobility of serine protease 2 (TMPRSS 2) and modulation of the function of the renin-angiotensin framework, both of which are strongly linked to ACE2; have been identified as molecular indicators of entry of SARS-CoV-2 into the host cells (Lukassen et al, 2020;Luo et al, 2020). In infectious disease clinical practice, physicians are regularly presented with variety of concerns about individual susceptibility among individuals who have the same sickness caused by an indistinguishable culprit.…”
Section: Preventive Measuresmentioning
confidence: 99%